The relevance of green building in creating a healing environment in hospital designs in Malaysia = Kerelevenan ‘Green Building’ dalam membentuk suasana pemulihan pada reka bentuk hospital di Malaysia - Aripin, Srazali; Othman, Rosniza; Mohd Nawawi, Norwina (Universiti Pendidikan Sultan Idris, 2015)
Green building is presently the buzz word in the construction industry in Malaysia. With the presence of Green Building Index rating tool, the building is perceived as an opportunity for developers and building owners to design and construct green as well as to achieve sustainable buildings that can save energy and water, healthier indoor environment, better connectivity to public transport, and adoption of recycling and greenery as well as reduce impacts on the environment. In the case of hospital buildings, where patients seek medical treatment and hospital staffs provide continuous 24 hour support, achieving sustainable building for a healing environment is important. In an effort to create an environment that is physically healthy and psychologically appropriate for hospital buildings, this paper aims to critically review the relevance of the green building concept in a sustainable development of a hospital. First, thematic reviews on the concepts of healing environment and green building, as well as the available rating tools for green buildings from other parts of the world were carried out. Assessment on the Green Building Index rating tool for hospital buildings in Malaysia was performed on the two public hospitals. Interviews were also carried out using structured questionnaire surveys on the selected respondents such as medical (doctors and nurses), management and maintenance personnel to gauge their views on green building concept for hospital. Preliminary findings indicated that the Green Building concept is perceived by staff to be relevant in hospitals in order to achieve an environment that is physically healthy and psychologically appropriate for patients, staff and visitors. The paper also highlighted other factors needed to achieve the green building rating scale for existing public hospital buildings in Malaysia.